Cost analysis of warranty based on lemon law with multiple failures and total downtime - Husniah, Hennie; K. Hermawan, K. Hermawan; B.P. Iskandar, B.P. Iskandar (Faculty of Economics and Business Mulawarman University, 2021)
Analysis of warranty costs is a topic that is widely studied in various finished product industries. One type of warranty that applies is a product warranty under Lemon Law. This guarantee under Lemon Law applies a lot to automotive products such as cars. Lemon Law is a law that protects consumers from poor quality new goods that are not in accordance with related product standards but can reach consumers. With this Lemon Law, consumers can return products that are proven to have a lemon condition in the hands of producers to then get a refund (replacement ) or replacement with a new similar product ( replacement ). The product can be claimed in a lemon condition if: (1) the car has been returned to the dealer four times because it needs to be repaired on the same problem / faulty part, but the dealer is unable to fix it satisfactorily; or (2) the car has been out of service for more than 30 days due to one or more damage. Analysis of warranty costs in this study includes replacement cases with compliance with conditions (1) only, replacement cases with fulfillment of conditions (2) only, and replacement cases with fulfillment of conditions (1) and conditions (2). A simulation method is designed to illustrate variations in the condition of the damage to the car during the warranty period as well as variations in repair time when damage occurs based on a particular distribution. The algorithm of the simulation is then modified and developed to determine the expected cost that fulfill the conditions (1) and (2).